Pelatihan Bahasa Arab : Mufrodat A’dho’ul Jismi dengan Metode Interaktif pada Anak-Anak di Majlis Darul Anwar kp. Sukajaga Desa Cihanjawar - Yayu Wahyudah; Rohendi Rohendi; Abdurrahman Shaleh (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The Arabic language training using an interactive learning method at Majelis Darul Anwar Kampung Sukajaga aimed to enhance children’s vocabulary in Arabic, particularly concerning body parts (a'dho'ul jismi). The method emphasizes active involvement of children through games and participatory activities, such as the